Strengthening Regional Agrarian Reform: Policy Assistance and Academic Drafting on Abandoned Land in Pangandaran Regency - Achmad Sodik Sudrajat; Riky Rinaldi Maulana; Nur Imam Taufik (Trescode Green Organization, 2024)
The service project was carried out as part of the efforts made by the Regional Government and DPRD of Pangandaran Regency to handle the issue of abandoned lands due to the lack of regional regulations concerning this matter. The objectives of the program were the strengthening of the capacity of the institutions through policy assistance in the making of the Academic Draft and the Raperda on the Inventory, Utilization and Management of Abandoned Lands. The program took the approach of collaboration and utilized the method of normative-juridical study, field observation, consultation and focus group discussions (FGD) with the involvement of the Regional Government, DPRD, BPN, Regional Agencies, Academics and Community representatives. The result was a well-prepared academic draft which includes philosophical, sociological and juridical foundation. Apart from generating the draft regulation, the program has increased the capacity of local government officials and members of DPRD in evidence-based policy making, increased cross-sectoral coordination, and created a common understanding on sustainable governance of abandoned lands. The Academic Draft serves as the scientific basis for formulating regional regulations and helps in developing an integrated land administration system in Pangandaran District. This community service indicates that policy assistance through participation is capable of improving institutional capacity, collaborative governance, and sustainable policy solutions for optimizing abandoned land management for the benefit of people's well-being and regional development.